FLORISTIC COMPOSITION AND PLANT DIVERSITY ANALYSIS OF ANBESSA FOREST IN WESEREN ETHIOPIA AND ITS CONRTIBUTION TO BIODIVESRITY CONSERVATION - Gudaye, Tamene Yohannes; Demissew, Sebsebe; Argaw , Mekuria; Edessa , Sutuma (International Journal of Research -GRANTHAALAYAH, 2022)
The study was conducted at Anbessa forest in Western Ethiopia with the objectives to make an assessment of plant diversity and plant community. A systematic sampling technique was used and a total of 30 sample plots each with 20 x 20 m were laid along the altitudinal gradient. A total of 118 plant species were identified which belong to 93 genera in 46 families. Out of which 14.41 % were Fabaceae (17 species), followed by Asteraceae 11.86 % (14 species), Poaceae 8.47 % (10 species) and Lamiaceae 5.93 % (seven species). Out of the 118 identified plant species, 33.05 % were trees, 11.86 % shrubs, 11.86 % climbers and the rest 43.22 % were herbs. The present study reported nine endemic plant species are present in Anbessa forest. Moreover, 29 plant species were recorded as new records for Wellega floristic region from Anbessa forest. Four plant communities were identified. In Anbessa forest Combretum collinum - Dombeya quinqueseta -Securidaca longepedunculata community was the most diverse community, whereas Oxytenanthera abyssinica - Combretum molle - Syzygium guineense subsp. macrocarpum community was the lease diverse with H′ 0.16. The result showed that, Anbessa forest can play a significant role in biodiversity conservation.